The Analysis of Teacher-Student Interaction on Student Motivation - Alda Uswatun Hasanah; Ratmanida Ratmanida (Journal of English Language Teaching, 2023)
Interaction has a positive impact on students learning because it can attract students’ attention and motivate them during the learning process. Especially in the English subject, students' interactions in the language classroom will help them develop both their language proficiency and their social skills. The aim of this study is to find out how the interaction takes place during the learning process and how does it affect the students learning motivation. This research involved 69 students of the 11th grade at SMA Negeri 2 Padang. This study used  descriptive method design. The written form of video recordings and questionnaire were used for the data collection. The result revealed that the dominant category for Teacher-Students pattern is Asks Questions, while the Students-Teacher pattern is Response. When asking questions and giving directions, the teacher dominantly used Bahasa Indonesia. Several of the questions and directions from the teacher are responded by the students mostly in Bahasa Indonesia as the way for the students to participate in the interaction. Moreover, the result revealed that there is a positive and significant relationship between classroom interactions and students' intrinsic and extrinsic learning motivation. Consequently, the classroom interactions between students and teachers affect the students’ learning motivation.